A life cycle assessment of the effect of intensification on the environmental impacts and resource use of grass-based sheep farming. (October 2016) - O'Brien, D.; Bohan, A.; McHugh, N.; Shalloo, L.
Abstract: Intensification is a strategy that is reported to increase the productivity and environmental performance of livestock farms, but most life cycle assessments (LCA) of livestock (particularly sheep) only consider greenhouse gas (GHG) or carbon footprint (CF). The goal of our LCA study was to assess the effect of intensification on several measures of environmental impact and resource use for grass-based sheep farms. The impacts we considered in addition to CF were acidification and eutrophication. The resource use measures we assessed were fossil fuel energy demand, land occupation and land use efficiency in terms of human digestible protein (HDP) production. Both environmental and resource use measures were expressed per kg of sheep live weight (LW) produced. The sheep production systems we assessed were Irish case study farms that represented average lowland, average hill, intensive lowland mid-season (IMS) and intensive early-season (IES) systems. Our results showed that the food-related environmental impacts and resource use of the average lowland sheep farm could be improved by intensifying grass and animal production. In addition, there was significant potential to increase production within area-based regulatory limits on nitrogen and phosphorus. However, increasing animal production by feeding more concentrate was less efficient and increased environmental impacts compared to increasing grass production, because concentrate required significantly more resources than pasture to produce and generated more emissions. There was limited potential to produce meat from the average hill farm that was located on marginal land. This generally led to the average hill farm having the highest product-related environmental impacts, but this system had the lowest nutrient surpluses per unit area. Modeling assumptions regarding carbon sequestration by grassland had a large effect on farm carbon footprints. The average hill farm had the highest carbon footprint when sequestration was excluded, but the opposite was the case when it was included. Therefore, we recommend clearly documenting the contribution of uncertain carbon sinks such as grassland sequestration to carbon footprints of sheep production systems. Additionally, we suggest that the assessment of land use efficiency should not be confined to HDP production and instead an index or scoring system should be used that accounts for the textile products and ecosystem services (e.g., landscape conservation) of sheep farms. The latter can be quantified using data from agri-environmental schemes or farm surveys and would provide additional important information on the environmental benefits of sheep farming. Highlights: We assessed the environmental impacts and resource use of four grass-based sheep farms differing in intensity. Intensifying animal production from grazed grass reduced food-related environmental impacts and resource use. Assumptions regarding carbon sequestration affected the order of farms carbon footprints. Sheep farms reliant on pasture produced more human digestible protein than they actually consumed. The potential to produce digestible protein from crops was greater than animals on lowland sheep farms